2020
DOI: 10.1002/smll.202004583
|View full text |Cite
|
Sign up to set email alerts
|

Fe1/TiO2 Hollow Microspheres: Fe and Ti Dual Active Sites Boosting the Photocatalytic Oxidation of NO

Abstract: Recently, single‐atom catalysts have aroused extensive attention in fields of clean energy and environmental protection due to their unique activity and efficient utilization of the active atoms. It is of great importance but still remains a great challenge to unveil the effect of single atoms on precise catalysis. Herein, it is reported that doping TiO2 hollow microspheres (TiO2‐HMSs) with single atomic Fe can boost the photoreactivity of TiO2‐HMSs towards NO oxidation due to the synergistic effects of atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 22 publications
(11 reference statements)
0
44
1
Order By: Relevance
“…Through first-principles calculations, Li et al [78] found that the Cr single-atom catalyst supported on graphene is the most promising single-atom catalyst for NO oxidation. Compared with precious metals, the 3D orbitals of transition metals Fe and Co do not form paired electrons, so they have unique activities [79]. In addition, the synergy between the double active sites of metal atoms can also be used to catalyze the oxidation of NO, so that the adsorption of NO and O 2 on the active surface is enhanced, and at the same time, the occurrence of side reactions is inhibited.…”
Section: Catalytic Oxidation Of No Xmentioning
confidence: 99%
“…Through first-principles calculations, Li et al [78] found that the Cr single-atom catalyst supported on graphene is the most promising single-atom catalyst for NO oxidation. Compared with precious metals, the 3D orbitals of transition metals Fe and Co do not form paired electrons, so they have unique activities [79]. In addition, the synergy between the double active sites of metal atoms can also be used to catalyze the oxidation of NO, so that the adsorption of NO and O 2 on the active surface is enhanced, and at the same time, the occurrence of side reactions is inhibited.…”
Section: Catalytic Oxidation Of No Xmentioning
confidence: 99%
“…[15,17,19,37,38] Photocatalysts with hollow structures have attracted great attention owing to manifold advantages including larger specific surface area, abundant active sites, shortened diffusion distance as well as improved light reflection and scattering. [37,[39][40][41][42][43][44] Therefore, the design of hollow S-scheme heterojunction photocatalyst is of vital importance to enhance photocatalytic performance.ZnIn 2 S 4 , as a typical reduction photocatalyst, stands out for its layered structure, narrow bandgap, suitable redox potentials, and good chemical stability. And it has been used for various photocatalytic applications including hydrogen production, CO 2 reduction, and organic degradation.…”
mentioning
confidence: 99%
“…[15,17,19,37,38] Photocatalysts with hollow structures have attracted great attention owing to manifold advantages including larger specific surface area, abundant active sites, shortened diffusion distance as well as improved light reflection and scattering. [37,[39][40][41][42][43][44] Therefore, the design of hollow S-scheme heterojunction photocatalyst is of vital importance to enhance photocatalytic performance.…”
mentioning
confidence: 99%
“…178,243 In addition to the CO 2 reduction reaction, photocatalysis based on SACs has also made some achievements in other reactions. 24,98,140,244 For example, Wang and co-workers designed a novel molten salt method (MSM) to prepare a TiO 2 -supported single Ni co catalyst for the hydrogen evolution reaction (HER). 24 In the MSM process, it is found that Ni atoms on TiO 2 are benecial to the formation of oxygen vacancies, which facilitate the transfer of charge and the reaction of hydrogen evolution.…”
Section: Electrocatalysis and Photocatalysismentioning
confidence: 99%